Implikasi Hukum Kebijakan Desentralisasi dalam Hubungan Kewenangan antartingkat Pemerintahan Negara Kesatuan - Andi Kasmawati (Fakultas Hukum Universitas Islam Indonesia, 2010)
The implication of post-new era decentralization has created the dynamic of the relation betweengovernment and district government. The authority of district governmental arrangement used to be centralized in Jakarta. Now, it is decentralized in districts. The focused problem of this research: first, how is the effect of decentralization policy on the relation of governmental inter-level in a united nation? Second, how is the conflict resolution of governmental inter-level authority in a united nation? This research used the constitutional law approach and conceptive approach. The normative and empiric research are done in central and district government. The data is collected through a literacy study and interview which is analyzed qualitatively. The result of the research has showed that; first, the policy of decentralization affects has positive impact which is improvement of efficiency and effectively in conducting the government matter, and improves community participation, conversely the negative impact is conflict of authority occurs as the result of imbalanced constitutional law, the primordial and nepotism potency. Second, the authority conflict is solved by perfecting the constitution, strengthening the real autonomy, and the optimizing assistance, supervision, and evaluation.Key words : Decentralization, united nation, and authority conflict